2007
DOI: 10.1002/cncr.22498
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of chronic myeloid leukemia in the imatinib era

Abstract: BACKGROUNDThere is paucity of data from developing countries on the efficacy and safety of imatinib mesylate in chronic myeloid leukemia (CML). The primary objective of this study was to document complete and partial cytogenetic responses to imatinib in all phases of CML. Secondary objectives included evaluations of complete hematologic response, safety, time to progression, and survival.METHODSTwo hundred seventy‐five patients in all phases of CML who received treatment with imatinib from January 2001 to Dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…In addition, a large multi-center study in France reported the frequencies of CP, AP and BC as 96.8%, 2.2% and 0.9%, respectively, at the time of diagnosis [18]. Therefore, our data strongly correlate with the data previously reported for Pakistan [20] and one possible explanation for this similarity may be that Pakistan is a neighboring country with similar ethnic demography and sociocultural factors.…”
Section: Resultssupporting
confidence: 87%
“…In addition, a large multi-center study in France reported the frequencies of CP, AP and BC as 96.8%, 2.2% and 0.9%, respectively, at the time of diagnosis [18]. Therefore, our data strongly correlate with the data previously reported for Pakistan [20] and one possible explanation for this similarity may be that Pakistan is a neighboring country with similar ethnic demography and sociocultural factors.…”
Section: Resultssupporting
confidence: 87%
“…We have previously reported marked improvements in cytogenetic response and sustained survival at longer follow-up with IM in our patients from Pakistan [3,7]. However, there is a paucity of data from developing countries on the long-term impact on QOL and the degree of comorbidity in patients receiving IM for the treatment of CP-CML.…”
Section: Introductionmentioning
confidence: 86%
“…Also, SCT can only be performed in a limited number of patients in Pakistan because the majority belong to a poor socioeconomic class and, hence, cannot afford to undergo the procedure. Moreover, poor living conditions and illiteracy put them at risk of recurrent infections [3]. Other treatment options have included hydroxyurea, which has few sideeffects but is of limited efficacy [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore important to establish if these results can be reproduced in Asian developing countries. A recently published trial from Pakistan shows a favorable result, similar to Western counties [4]. However, the efficacy of IM in Indian patients seems poorer [5].…”
Section: Introductionmentioning
confidence: 93%